An Investigation on an Early Byzantine Higher School in Russian Historiography - Bolgov, Nikolai N.; Bolgova, Anna M.; Ryabtseva, Marina L.; Lopatina, Marina Yu.; Semecheva, Elena A. (Journal of History Culture and Art Research, 2017)
This article deals with the main approaches and achievements in the Russian studies of Late Antiquity in-between period from Antiquity to the Middle Ages. The current literature has an attempt to highlight the activities of leading scientists and their works as well as the activities of various regional schools on studying the higher schools of the Early Byzantium. The authors of the article came to the conclusion that there are some difficulties with the terminology in Russia, also there is no common understanding of this transitional time and many specialists prefer to work with narrow-focused material. Furthermore, there remains a ‘format’ of antiquists, Byzantinists and medievalists what makes integrative researches more difficult. To reveal these issues, the current study investigates the academic bibliography.